2008
DOI: 10.1590/s1413-81232008000500008
|View full text |Cite
|
Sign up to set email alerts
|

A situação atual do mercado da saúde suplementar no Brasil e apontamentos para o futuro

Abstract: A situação atual do mercado da saúde suplementar no Brasil e apontamentos para o futuroThe current situation of the private health plans and insurance market in Brazil and trends for the future

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
27

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 5 publications
0
9
0
27
Order By: Relevance
“…Under this perspective, the quest for a treatment, at least, as effective and less costly compared to others currently covered by companies becomes key to guaranteeing the financial sustainability of the system. This is required especially if we consider the current scenario of growing casuistic and decreasing profitability of supplementary healthcare insurance companies (Albuquerque et al, 2008), in addition to the increased population life expectancy (Azevedo, 2010). Certolizumab pegol in several studies has been shown as effective and safe as other anti-TNF agents available to treat CD (Shao et al, 2009;Singh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Under this perspective, the quest for a treatment, at least, as effective and less costly compared to others currently covered by companies becomes key to guaranteeing the financial sustainability of the system. This is required especially if we consider the current scenario of growing casuistic and decreasing profitability of supplementary healthcare insurance companies (Albuquerque et al, 2008), in addition to the increased population life expectancy (Azevedo, 2010). Certolizumab pegol in several studies has been shown as effective and safe as other anti-TNF agents available to treat CD (Shao et al, 2009;Singh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…9.656/98 e a criação da ANS, ter se verificado uma melhoria na quantidade e qualidade de dados sobre o mercado de saúde suplementar, ele ainda é pouco conhecido e considerado no planejamento do sistema de saúde no país. Essa questão assume grande relevância, em face da abrangência do setor, assim como da sua forte relação com o setor público 10 .…”
Section: Discussionunclassified
“…Conforme Albuquerque et al (2008), as operadoras estão organizadas em modalidades, segundo seu estatuto jurídico: …”
Section: A Saúde Suplementar E No Brasilunclassified